A monoclonal antibody-based copro-ELISA kit for canine echinococcosis to support the PAHO effort for hydatid disease control in South America. - Noelia Morel; Gabriel Lassabe; Susana Elola; Mauricio Bondad; Silvia Herrera; Carlos Marí; Jerold A Last; Oscar Jensen; Gualberto Gonzalez-Sapienza (PLoS Neglected Tropical Diseases, 2013)
Cystic echinococcosis is still a major concern in South America. While some regions show advances in the control of the disease, others have among the highest incidence in the world. To reverse this situation the Pan American Health Organization (PAHO) has launched a regional project on cystic echinococcosis control and surveillance. An early concern of the program was the lack of a standardized diagnostic tool to monitor infection in dogs, a key target of control programs. Under this premise, we have developed a new copro-ELISA test after extensive screening of a large panel of monoclonal antibodies (MAbs) and polyclonal sera, which performs with high standards of sensitivity (92.6%) and specificity (86.4%) as established by necropsy diagnosis of dogs. The key component of the test, MAbEg9 has a convenient IgG isotype and reacts with a periodate-resistant epitope found in high molecular weight components of the worm. Time-course analysis of experimentally infected dogs showed that even animals with a very low number of parasites could be detected as early as day 20 post infection. The test was formulated in a ready-to-use kit format with proven stability of each component for a minimum of 3 months at room temperature. This characteristic facilitates its standardized use and shipping to other laboratories, which was demonstrated by the identical results obtained by two different laboratories in Peru and our own laboratory when a large number of field samples were analyzed independently in a blind fashion.